Postmortem Changes in pH, Color, Drip Loss, and Non-Protein Nitrogen in Beef Liver and Lungs During Storage in Refrigerator - Lukman, Denny; Pisestyani, Herwin; Latif, Hadri; Sudarnika, Etih; Bachrum, Mirnawati (Acta VETERINARIA Indonesiana, 2020)
Beef offal are consumed by people in some countries specifically in Asia.  Beef liver and lungs are favorite food which are used as meat in traditional food.  The objective of this study was to determine the postmortem changes in pH, color, drip loss, and non-protein nitrogen (NPN) content in beef liver and lungs during storage in refrigerator (3-4 ºC) until 5 d (120 h) after slaughter.  The beef liver and lungs were collected from the abattoir and transported in cool box (